Digitalizing Grammatical Terminology in Uzbek: Toward an Electronic Dictionary of Borrowed Terms (Texas Journal of Philology, Culture and History, 2025)
The present article discusses the importance and urgency of developing an electronic dictionary of borrowed grammatical terms in Uzbek linguistics. Despite recent efforts toward the indigenization of certain terms, the fundamental grammatical terminology remains largely influenced by Greek and Russian origins. Existing explanatory dictionaries, widely used by researchers and educators, are not yet available in digital form, which limits their accessibility and usability in modern linguistic studies and education. This study proposes a systematic approach to compiling a comprehensive electronic dictionary that includes a database of borrowed grammatical terms, methods of their assimilation, and detailed linguistic analysis covering etymology, semantics, and phonology. Furthermore, it emphasizes the integration of modern linguistic technologies such as annotation, lemmatization, parsing, and tagging to enhance the dictionary’s functionality and searchability.